The impact of learning engagement on the subjective well-being of disadvantaged older adults in China - Li, Yuan; Shi, Huiqin; Yuan, Yaya; Zeng, Ruirang; Bai, Binggui; Sun, Lixin (Frontiers in Public Health, 2023)
Due to social transformation, economic reform, and the advent of an aging society, the number of disadvantaged older adults in China is increasing. The living conditions of the disadvantaged older adult groups determine society's stability to a certain extent. How to make their lives happier in their old age, promote their subjective well-being, and realize the "enjoyment of the older adults" is of great practical significance in improving social civilization and building a harmonious society. This study is based on the survey data from the lower counties of Ningbo city in Zhejiang province, where there is a high concentration of older learners, and used SPSS 27.0 software to process the data. The results indicated the following: the subjective well-being of disadvantaged and non-disadvantaged older adults differed significantly; learning engagement had a significant effect on enhancing the subjective well-being of disadvantaged older adults, and all dimensions of learning engagement had a significant positive relationship with subjective well-being (SWB).Compared to non-disadvantaged older adults, learning engagement had a more significant contribution to the SWB of disadvantaged older adults.